A top–down fabricated gold nanostrip on a silicon-on-insulator wafer: a promising building block towards ultra-compact optical devices. Issue 3 (13th January 2021) - Zhang, Fuping; Liu, Weikang; Chen, Li; Guan, Zhiqiang; Xu, Hongxing
Abstract : An optimized thin silicon layer on a substrate can increase the coupling efficiency and suppress the leaky loss. Abstract : A plasmonic waveguide is a fundamental building block for high speed, large data transmission capacity, low energy consumption optical communication and sensing. Controllable fabrication and simultaneous optimization of propagation loss and coupling efficiency with free space light are essential for the realization of ultra-compact passive and active plasmonic components. Here, we proposed gold nanostrips on a silicon-on-insulator wafer as plasmonic waveguides and first demonstrated the direct free-space light coupling and end-scattering detection of the top–down fabricated plasmonic waveguide. The scattering intensity from the terminal of a 6 μm long nanostrip can be improved experimentally over 34 times larger than that on the silica substrate. The controllable fabrication process renders the gold nanostrip on a silicon-on-insulator substrate a promising building block for ultracompact, monolithic integration and CMOS-compatible plasmonic devices in optical communication and sensing.